Review on Effects of Logistics Practices and Information Sharing on Supply Chain Performance - Gebisa, Diriba Ayele (International Journal of Marketing Research Innovation, 2019)
Today companies no longer compete merely as an independent business but rather as supply chains. Individual businesses no longer operate in isolation and neither should their strategic orientation be wholly individualistic. This attracted supply chain management concept to be used. Supply chain management primarily designed by firms to get competitive advantage over the rival firms and to overcome the intense global competition coming from globalization, innovation, free trade and economic cooperation formed in different region. The concept led to cooperation and integration among firms and with their suppliers, distributors, consumers, and transport agency. It is totally systematic coordination and management from upstream to downstream paths of an organization. The importance and research interest in supply chain management are growing from time to time; however, the number of professional materials and well-organized review literature is limited relative to the growing trend of the area. Therefore, this paper reviewed different supply chain management articles, reports, and books by concentrating on logistics practices and information sharing on supply chain performance to develop a well-organized research article that advances supply chain management understanding. Under the logistics practices, the major variables discussed were the effect of the road network, transportation cost, facility location, waiting time, inventory management and mode of transportation, whereas the effect information sharing discussed from the viewpoints of the level of information sharing and quality of information on supply chain performance.